PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA TAHUN 2021 (STUDI KASUS DESA GOISO OINAN KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI) - Julia Sageileppak; A An Arief Jusuf (Jurnal Cakrawala Ilmiah, 2023)
The purpose of this research is to understand how the role of village leaders in Goiso Oinan Village, North Sipora District, Financial Management. Material acquisition methods obtained by using interviews, documentation and questionnaires. A total of 14 people were carried out in the survey, namely 7 village administrators, including the head of the BPD, the village secretary, the head of the finance section, the head of the planning section, the head of the governance, administration and hamlet heads, 1 village head and 6 community leaders. A qualitative descriptive method was used in this observation by adopting a case study in Goiso Oinan Village, Sipora Utara District, Mentawai Islands Regency. The findings from this study clearly show that the role of village officials in Goiso Oinan Village can be accounted for in managing village funds through the implementation of their tasks. Goiso Oinan Village has carried out its duties in stages which include planning, implementation, administration, reporting and accountability. Each village apparatus is responsible for carrying out their functions in accordance with applicable regulations. In addition, the village has also reported transparently by submitting the Realization Report on the Implementation of the APBDes and ADD as proof of their accountability